Crocodile Dundee II [videorecording (DVD)] - Cornell, John, 1941-; Hogan, Paul, 1939-; Kozlowski, Linda; Meillon, John (Paramount, 2001)
Continuing the adventures of the eccentric Australian, Crocodile Dundee, he and his beautiful girlfriend are threatened by a ruthless gang of drug dealers. Dundee evens the odds by leading the hoods to his turf, the Australian outback.